Advances in the development of new biologics in inflammatory bowel disease - Ungar, Bella (Ann Gastroenterol, 2016)
Biologics have revolutionized the therapeutic approach in inflammatory bowel disease (IBD). Anti-tumor necrosis factor (anti-TNF) agents infliximab and adalimumab currently constitute the major biological therapy in IBD. Additional anti-TNFs such as golimumab and other new biologics are currently being developed for both anti-TNF-naïve and -resistant patients. These include anti-integrins (vedolizumab and etrolizumab), a JAK inhibitor (tofacitinib) and an anti-anti-interleukin (IL)-23 and IL-12 antibody (ustekinumab), among additional drugs in development. The following review discusses the indications, efficacy and safety issues for these novel medications.